PEDAGOGICAL ADVANTAGES OF USING SOCIAL MEDIA TO IMPROVE SPEAKING SKILLS (SCIENCE TIME JOURNAL, 2026)
The rapid development of digital technologies and the widespread use of social media platforms have significantly transformed modern language education. Social media has emerged as an effective pedagogical tool for improving speaking skills, particularly in foreign language learning contexts. This article explores the pedagogical advantages of using social media platforms such as YouTube, Instagram, Telegram, Facebook, and TikTok to enhance learners’ oral communication abilities. These platforms provide authentic language input, real-life communication opportunities, and interactive environments that foster learner engagement and motivation. Through synchronous and asynchronous communication, learners can practice pronunciation, fluency, vocabulary usage, and pragmatic competence in meaningful contexts. Moreover, social media supports learner autonomy, collaborative learning, and continuous exposure to the target language beyond the classroom. The study highlights how social media encourages confidence building, reduces speaking anxiety, and facilitates intercultural communication. The findings suggest that integrating social media into speaking instruction can significantly improve learners’ communicative competence when used strategically and pedagogically.